ANALISIS YURIDIS PERTIMBANGAN HUKUM HAKIM DALAM PUTUSAN NOMOR : 22/PDT.G/PA.Spn - NIM. A1011171170, MUHAMMAD FAKHRI SA’I (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT This research discusses a case study at the Sungai Banyak Religious Court with number 22/PDT.G/2022/PA.Spn. Basically, a panel of judges must consider a decision regarding the individual conditions of the plaintiff and defendant regarding a case between the mother as the plaintiff and The father is the defendant in deciding child custody (hadhanah) for a child who is 5 years old or not yet an adult (mumayyiz). The sociological basis of law can embrace the community and court environment. The crux of the problem is that the plaintiff wants the judge to immediately determine custody of the child and ask for a solution to the problem regarding the Family Card being withheld by one of the parties, of course this causes difficulties for the plaintiff when they want to take care of the child